Peran Ilmu Antropologi bagi Karya Misi Gereja: Studi Interdisipliner bagi Penerapannya dalam Pelayanan Pastoral dan Kateketik Gereja - Agrindo Zandro (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2024)
The missionary work of the Church today often experiences deadlock and even failure as a result of the work of the wrong mission strategy, not on target, or not in accordance with the context of the lives of the faithful. To realize an appropriate and effective mission, the Church needs to conduct an interdisciplinary study between theology of mission and other sciences, one of which is anthropology. This science can provide accurate and efficient information related to the condition of the people so that the mission of the Church can truly enter the context of the lives of the faithful in a particular area and thus the gospel of truth and joy can be felt by the people. The purpose of this study is to describe the meaning and important role of anthropology, especially applied anthropology for the mission of the Church today, namely in pastoral and catechetical services. The methodology used is a qualitative method by applying a literature study, namely research on books and scientific articles as well as related Church documents. This study found that the science of anthropology is very useful for the mission of the church, especially anthropology has contributed to developing the treasures of Christian theology. The unique contribution of this study is contextual and up-to-date knowledge about mission strategies that can embrace the people of God in all places and times.